THE USE OF SPRINGS IN STATIC ANALYSIS OF STRUCTURES TO ACCOUNT FOR SHORT-AND LONG TERM SUBGRADE DEFORMATIONS - Worku, Asrat (Zede Journal of Ethiopian Engineers and Architects, 2023)
The theory of elasticity of continua is employed to show the background of spring formulas that are introduced at the bases of structures to account for immediate static deformation of soils. This is followed by providing sets of such valuable formulas for use in practical modeling of structures founded on deformable soils. Additional spring formulas that account for primary and secondary consolidation settlement are derived It is shown that these vertical springs can be joined in series to account for all types of soil deformation immediate, primary consolidation, and secondary consolidation or creep. The application of the springs is illustrated using a simple buildingframe subjected to gravity loads only The internal forces in the structural members with and without flexible base elements showed notable differences. The significance of the introduction of flexible-base elements in taller and more rigid structures subjected to lateral loads can be expected to be even larger. The influence of the consolidation springs could particularly be more significant if different foundation elements of a structure rest on compressible layers of different properties and varying thickness. A companion paper deals with a parametric study on the influence of elastic base springs, in which the height and type of the structural system, the soil type, and the embedment depth ofthefoundation are varied